PENGARUH TEMAN SEBAYA DAN LINGKUNGAN KELUARGA TERHADAP KECERDASAN SOSIAL SISWA DI MTS NEGERI 7 AGAM - Azie Utami Erlin; Syawaluddin; Afrinaldi; M Arif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low level of students’ social interaction skills at MTs Negeri 7 Agam, indicating problems in their social intelligence. This condition is assumed to be influenced by peer relationships and family environment, which may not optimally support students’ social development. Therefore, this study aims to analyze the effects of peers, family environment, and both variables simultaneously on students’ social intelligence. This research employs a quantitative approach with an associative design. The population consists of 253 students, with a sample of 98 students selected using proportional random sampling based on the Taro Yamane formula. The research instrument is a questionnaire covering peer influence, family environment, and social intelligence variables. Data analysis is conducted using simple linear regression and multiple linear regression to test the research hypotheses. The results show that peers have a significant effect on social intelligence, contributing 9.9%. The family environment also has a significant effect with a higher contribution of 30.9%. Simultaneously, peers and family environment significantly influence students’ social intelligence with a combined contribution of 34.3%. These findings highlight the important role of both factors in enhancing students’ social intelligence.